1995
DOI: 10.1101/gad.9.22.2780
|View full text |Cite
|
Sign up to set email alerts
|

CLN3, not positive feedback, determines the timing of CLN2 transcription in cycling cells.

Abstract: Transcriptional activation of the budding yeast CLNl and CLN2 genes during the late GI phase of the cell cycle has been attributed to a positive feedback loop, wherein the transcription of both genes is stimulated by the accumulation of their protein products. We demonstrate that in cycling cells CLN2 does not play a role in determining the timing of its own transcriptional activation. First, we show that CLN3 alone is sufficient to maximally activate CLN2 transcription. Cells that lack functional CLNl and CLN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
178
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 53 publications
10
178
0
1
Order By: Relevance
“…1A). These data are consistent with previous reports showing that CLN3 is expressed rapidly in response to fresh nutrients and subsequently activates the other G1 cyclins, CLN1 and CLN2 (40)(41)(42). We therefore hypothesized that CLN3 transcription might be similarly driven by the acetyl-CoA-induced acetylation of histones present in its regulatory region.…”
Section: Resultssupporting
confidence: 81%
“…1A). These data are consistent with previous reports showing that CLN3 is expressed rapidly in response to fresh nutrients and subsequently activates the other G1 cyclins, CLN1 and CLN2 (40)(41)(42). We therefore hypothesized that CLN3 transcription might be similarly driven by the acetyl-CoA-induced acetylation of histones present in its regulatory region.…”
Section: Resultssupporting
confidence: 81%
“…Mcml also controls expression of two genes, SWI4 and CLN3, which are known to be critical for entry into S phase and the transcription of the G1 cyclins CLN1 and CLN2 (Dirick et al 1995;Stuart and Wittenberg 1996). Our studies with CLN3 and SWI4 heterozygotes indicate that these proteins are not in excess during the cell cycle.…”
Section: Discussionmentioning
confidence: 63%
“…Cln3 and Swi4 play critical roles in activating the burst of CLN1 CLN2 transcription in late G1 (Nasmyth and Dirick 1991;Ogas et al 1991;Dirick et al 1995;Stuart and Wittenberg 1996), but the mechanism of that activation is not understood. We have shown that SWI4 and CLN3 transcription is ECB regulated and peaks just before the peak of CLN1 and CLN2 transcription.…”
Section: Swi4 and Cln3 Are Both Rate Limiting For The G I To S Transimentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The levels of both proteins are controlled by the same molecular mechanisms: the CLN1 and CLN2 genes are expressed periodically during the G 1 /S transition by the transcription factor SBF, [17][18][19] and the Cln1 and Cln2 proteins are degraded via the SCF Grr1 ubiquitinligase. [20][21][22] Compared with single mutants, the cln1 cln2 double mutant shows severe growth defects, 23,24 indicating a functional overlap between these two cyclins. In fact, the extensive work performed on these cyclins has revealed that they take part in many common functions, such as induction of growth polarization and budding, [25][26][27] SPB duplication, 28 degradation of CDK-inhibitors Far1 and Sic1, [29][30][31][32] inactivation of the APC ubiquitin-ligase complex, 33,34 repression of pheromone-induced transcription or stimulation of pseudohyphal growth.…”
Section: Molecular Basis Of the Functional Distinction Between Cln1 Amentioning
confidence: 99%